Terpyridine and 2, 6-di(1H-pyrazol-1-yl)pyridine substituted cyclotri- and polyphosphazene ruthenium(II) complexes: Chemical and physical behaviour. (8th January 2015) - Davidson, Ross J.; Ainscough, Eric W.; Brodie, Andrew M.; Jameson, Geoffrey B.; Waterland, Mark R.; Allcock, Harry R.; Hindenlang, Mark D.
Abstract : Graphical abstract: A series of cyclotriphosphazene and polyphosphazene ruthenium(II) compounds substituted with pendant 2, 2′:6′, 2″-terpyridine (terpy) or 2, 6-di(1 H -pyrazol-1-yl)pyridine (bpp) moieties have been synthesised. X-ray crystallography, in conjunction with spectroscopic and computational studies, has been used to compare the small molecule complexes with their polymeric analogues. Abstract: The synthesis of a series of cyclotriphosphazene and polyphosphazene ruthenium(II) compounds is reported using 2, 2′:6′, 2″-terpyridine (terpy) and 2, 6-di(1 H -pyrazol-1-yl)pyridine (bpp) pendant ligands. X-ray crystallography, UV–Vis and resonance Raman spectroscopy have been employed to gain an insight into the physical and coordination behaviour of these complexes and indicate that both the small molecule and their polymeric analogues contain coordinated Ru in an octahedral 'N6 ' environment. The results reveal a difference between the chemistry of the ruthenium(II)-bpp-terpy and ruthenium(II)-bis-terpy complexes and demonstrate a means of grafting functional groups to a polyphosphazene backbone under mild conditions.